SITUASI TERKINI VEKTOR DENGUE [Aedes aegypti Lin] DI JAWA TENGAH, INDONESIA - Sayono, S. (KEMAS: Jurnal Kesehatan Masyarakat, 2016)
Dengue viruses infection spread world widely around the world causing 3,97 milliard people at risk, including Indonesian. Anti-dengue virus have not been available so that the prevention efforts were focused on controlling of Aedes population. Aim of this study is to understand the recent situation of Ae. aegypti mosquitoes in Dengue endemic areas. Dengue vector survey involved 20 houses around the Dengue patient’s house in six districts in Central Java Province, and the domestic water containers as object. The measured variables are container characteristics and mosquito larvae existence. Larvae were reared to become mosquito stadia, identified and subjected to insecticide susceptibility test. Ae. aegypti population indices (House index, Container index and Breteau index) ranged 27.3-55.2, 19.1-53.8, and 44.8-72.7 percents. Mosquito larvae were found in seven types of container, respectively. Mortality rate of mosquitoes in bioassay test were 17%, 67% and 100% based on permethrin-0.75%, Deltamethrin-0.05% and Malathion-5% compounds.    Keywords: Aedes aegypti, Dengue, endemic, Central Java